Interfacial lithiation induced leapfrog phase transformation in carbon coated Se cathode observed by in-situ TEM. (June 2018) - Li, Yonghe; Lu, Junxia; Cheng, Xiaopeng; Shi, Huifeng; Zhang, Yuefei
Abstract: Selenium (Se), a congener of Sulphur (S), is widely used as a cathode material for high energy-density lithium-ion batteries, named Li–Se batteries. It has been found that nanostructured Se confined in carbonaceous can lead to significantly improved rate capability and cyclic performance. However, the underlying mechanism of carbon coatings in view of surface/interface electro-chemo-mechanical effect at nanoscale remains poorly unexploited. Herein, equipped with in-situ transmission electron microscopy (TEM), we have investigated the type of lithium ions transportation, phase transformation, and coupling mechanical behavior of carbon conformably coated Se nanowire (NW) cathode reacted with Li. Intriguingly, We find a unique lithiation mechanism that the "leapfrog phase transformation" occurs at interface between carbon coating and Se NW cathode. The increasingly accumulated Li ions in leapfrog buckled region as a new platform would react with Se to form crystalline Li2 Se from surface to interior. More importantly, this interfacial diffusion pathway of Li ions uniquely differs from the surface-coating directed Li transportation engineered where in Li ions initially diffuse into coatings and then react with core materials of electrodes. Furthermore, we note a threshold diameter region of Se NWs with 115–120 nm, above which the uniform carbon coating ( 8.5 nm) shows remarkable crack and even delimitation after fully lithiation form. These observations provide reliable guidelines for the design of high-performance lithium-ion batteries by interface and surface engineering. Graphical abstract: We real time visualized the dynamical electrochemical lithiation – delithiation process in Se@carbon nanowires by in-situ transmission electron microscopy (TEM). The unique interfacial lithiation channel, leapfrog phase transformation, and size-dependent coating crack were jointly observed, which provides a new insight into the mechanism of Li-Se batteries systerm. fx1 Highlights: A unique lithiation mechanism that the "leapfrog phase transformation" occurs at interface of the core-shell structure. The interfacial diffusion pathway of Li ions and reversibility of phase transformation are both observed. A threshold diameter of Se NWs with 115–120 nm appears, above which the carbon coating ( 8.5 nm) shows crack.